Sward Diversity Modulates Soil Carbon Dynamics After Ploughing Temporary Grassland - Hendrik P. J. Smit; Hanna Anders; Christof Kluß; Friedhelm Taube; Ralf Loges; Arne Poyda (Agriculture)
Grasslands are crucial for sequestering carbon underground, but disturbances like ploughing can lead to significant soil organic carbon (SOC) loss as CO2, a potent greenhouse gas. Thus, managed grasslands should be maintained to minimize GHG emissions. A field study was carried out to investigate how varying sward diversity influences soil respiration following the ploughing of temporary grassland. This study investigated the extent of CO2 emissions from different species mixtures immediately after ploughing, as well as C losses when straw was added to plots, over a 142-day period. The species mixture treatments consisted of a binary mixture (BM), a tertiary mixture (TM), and a complex mixture (CM), which were compared to two bare plot treatments, one of which was also ploughed. The highest CO2 flux occurred immediately after ploughing and was observed in the BM treatment (1.99 kg CO2-C ha−1 min−1). Accumulated CO2 emissions ranged from 0.4 to 14.8 t CO2 ha−1. The ploughing effect on CO2 emissions was evident for bare soils, as ploughing increased soil aeration, which enhanced microbial activity and accelerated the decomposition rate of soil organic matter. However, different mixtures did not affect the C turnover rate. Adding straw to treatments resulted in 43% higher CO2 emissions compared to bare plots. The BM treatment likely induced a higher priming effect, suggesting that the incorporated straw, under different sward residues, influenced CO2 emissions more than the mechanical disturbance caused by ploughing. Findings suggest that using complex species mixtures can be recommended as a strategy to reduce CO2 emissions from incorporated biomass and minimize the priming effect of native soil carbon.